Robot-assisted minimally invasive thoraco-laparoscopic esophagectomy versus minimally invasive esophagectomy for resectable esophageal adenocarcinoma, a randomized controlled trial (ROBOT-2 trial) - Tagkalos, Evangelos; van der Sluis, P. C.; Berlth, Felix; Poplawski, A.; Hadzijusufovic, E.; Lang, H.; van Berge Henegouwen, M. I.; Gisbertz, S. S.; Müller, Beat P.; Ruurda, J. P.; Schiesser, M.; Schneider, P. M.; et al. (BMC cancer, 2021)
Background: For patients with esophageal adenocarcinoma or cancer of the gastroesophageal junction, radical esophagectomy with 2-field lymphadenectomy is the cornerstone of the multimodality treatment with curative intent. Both conventional minimally invasive esophagectomy (MIE) and robot assisted minimally invasive esophagectomy (RAMIE) were shown to be superior compared to open transthoracic esophagectomy considering postoperative complications. However, no randomized comparison exists between MIE and RAMIE in the Western World for patients with esophageal adenocarcinoma. Methods: This is an investigator-initiated and investigator-driven multicenter randomized controlled parallel-group superiority trial. All adult patients (age ≥ 18 and ≤ 90 years) with histologically proven, surgically resectable (cT1-4a, N0-3, M0) esophageal adenocarcinoma of the intrathoracic esophagus or adenocarcinoma of the gastroesophageal junction and with European Clinical Oncology Group performance status 0, 1 or 2 will be assessed for eligibility and included after obtaining informed consent. Patients (n = 218) with resectable esophageal adenocarcinoma of the intrathoracic esophagus or adenocarcinoma of the gastroesophageal junction are randomized to either RAMIE (n = 109) or MIE (n = 109). The primary outcome of this study is the total number of resected abdominal and mediastinal lymph nodes specified per lymph node station.